Eksperimen Pembelajaran Matematika Dengan Strategi Learning Start With A Question (Lsq) Dan Information Search (Is) Terhadap Hasil Belajar Matematika Ditinjau Dari Kepercayaan Diri Siswa Kelas VIII SMP Al Islam Kartasura - Arintawati, Amelia Kus, Drs. Ariyanto, M.Pd (2017)
The purpose of the research are to analyze: (1) the effect of learning Learning Start With A Question and Information Search on learning outcomes. (2) the effect student active for learning outcomes. (3) the interaction between learning methods Learning Start With A Question and Information Search of self confidence on learning outcomes. Type of the reseach quantitative with experimental design. Sample where taken by Cluster random sampling of the population of all students of class VIII SMP Al Islam Kartasura academic year 2016/2017. Data collection techniques by using questionnaires, tests and documentation. Before to the analyze, first tested the normality and homogeneity test. The hypotesistent use unvalance two way analysis of variance with α = 5%. The result of this study showed: (1) there was the effect of learning methods Learning Start With A Question and Information Search on learning outcomes. (2) there was the effect student self confidence for learning outcomes. (3) there was not interaction between learning methods Learning Start With A Question and Information Search of self confidence on learning outcomes.